Peningkatan Disiplin Aparatul Sipil Negara Melalui Kesadaran Diri (Self Awarrnes) - Kusuma, Rhendra (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Work discipline is an important aspect in the performance of State Civil Apparatus (ASN) as public servants. However, the level of ASN discipline is still a challenge, with various problems such as non-compliance with work rules, lateness, and lack of responsibility. This study aims to improve ASN discipline through a self-awareness approach. Self-awareness is the ability to understand strengths, weaknesses, emotions, and self-motivation that can encourage ASN to improve self-control and responsibility for those assigned. This research method uses a quantitative approach with a quasi-experimental design involving a number of ASN in the district government environment as respondents. The intervention provided was in the form of training and guidance to improve ASN self-awareness in the context of professionalism and work discipline. Information was collected through questionnaires before and after the intervention, and analyzed using statistical tests to see significant changes in the level of work discipline. The results of the study showed that after the self-awareness intervention, there was a significant increase in ASN work discipline, especially in terms of compliance with rules, increasing time effectiveness, and individual responsibility. ASN who have high self-awareness tend to be more disciplined and responsible in carrying out their duties, because they have a better understanding of the impact of their behavior and performance on public services. In conclusion, increasing self-awareness can be an effective strategy in improving ASN work discipline. This finding provides an important influence for the government in designing training and development programs that not only focus on technical skills, but also on psychological aspects such as self-awareness. Thus, it is hoped that ASN discipline and performance can continue to be improved in order to support the creation of better and more efficient public services.